Purvi Mehta-Bhatt’s report from parallel sessions of the IFPRI 2020 confernce - Mehta-Bhatt, Purvi (International Food Policy Research Institute, 2014)
Purvi Mehta-Bhatt, Regional Representative, South Asia, International Livestock Research Institute (ILRI), India, at the IFPRI 2020 conference on Building Resilience for Food and Nutrition Security, May 15-17, 2014, Addis Ababa, Ethiopia. More information athttp://www.2020resilience.ifpri.info